From gold money to fictitious money - F. S. Prado, Eleutério (Brazilian Journal of Political Economy, 2016)
In the nineteenth century, money appear primarily as gold. In the twenty-first century, it appears as strictly fiduciary money. It is known that Marx said very clearly that the golden money was the effective basis of the monetary and credit system. Had the historical development finally shown that his theory of value and money would be false? Marxists have struggled continually with this problem. This paper tries to show that exist a simple and good answer to this crucial question. It comes just developing a little the dialectics of commodities and money found on Marx’s Capital. JEL Classification: B51; E50.